Perimesencephalic hemorrhage and vessel variants - Pechlivanis, Ioannis; Shang, F.; Harders, A.; Schulte-Altedorneburg, G.; Nölte, I.; Schmieder, Kirsten (Central European neurosurgery, 2011)
BACKGROUND: In 95% of patients with an apparently normal distribution of blood using unenhanced computed tomography (CT), no ruptured aneurysm for a perimesencephalic subarachnoid hemorrhage (PMSAH) will be detected. In general, the clinical course of these patients is more favorable than that of patients with a detected ruptured aneurysm. We wanted to assess whether vessel variants of the vertebro-basilar circulation are more common in patients with PMSAH than in patients with SAH caused by intracranial aneurysms. Furthermore, we wanted to investigate whether CT angiography (CTA) as a sole diagnostic modality in PMSAH is sufficient. - MATERIAL AND METHODS: In patients diagnosed with PMSAH (study group), a CTA was performed routinely as the first-line diagnostic modality. If no aneurysm was found, digital subtraction angiography (DSA) was done. CTA and DSA data sets were analyzed for the presence of an intracranial aneurysm. Furthermore, the diameter of the arteries in the posterior circulation was measured. Special attention was paid to vascular variations. Moreover, CTA and DSA findings were compared with data sets from patients with SAH and an intracranial aneurysm of the posterior circulation (control group). - RESULTS: Between January 2002 and June 2007, 28 patients with PMSAH were enrolled in our study. All patients received both CTA and DSA. Furthermore, 28 control data sets were analyzed. Image analysis showed hypoplasia of one or more arterial vessels in 92.9% of PMSAH patients vs. 60.7% of the patients in the control group (p=0.010). Moreover, aplasia of one vessel occurred significantly more often in the study group (53.6%) than in the control group (21.4%; p=0.026). 8 patients in the control group vs. no patients in the study group showed no vessel variants (p=0.004). DSA did not show additional vessel variants, nor did it provide additional information regarding the vessel diameter. - CONCLUSION: Interestingly, an increased number of arterial vessel hypoplasia was detected in PMSAH patients. Furthermore, CTA as a sole diagnostic modality in patients with typical PMSAH is sufficient.
Gesehen am 06.10.2022